Money inside multi-level political organisations: the case of Brazil - Pinto Medeiros, Akira (2021)
This Master\'s Thesis explores political parties financing in multi-level systems, using Brazil as a case. Before diving into our case, we perform a deep literature review on Political Parties and its\' organisation, and on political parties financing. Later on, we move our eyes to Brazilian Political Parties\' regional branches financing between 2015 and 2018, in order to explore our case. By taking advantage of the fact that Brazilian parties became more dependent on Public financing, money transfers between National Executive Committees (NECs) and their hierarchically inferior units (regional branches) were tracked in order to assess if regional branches with representation on its\' NEC, end up receiving more money. This movement sheds light on Brazilian Political Parties\' internal politics and the regional branches\' influence over its\' NEC, suggesting that not only formal but also informal mechanisms are important to explain how money is divided internally. Our hypotheses can be described as: (I) Regional branches with a presence inside its\' hierarchically superior unit, have more influence on the party\'s political and strategic decisions (THORLAKSON, 2009; DETTERBECK, 2012; PANEBIANCO, 1995), and will consequently end up receiving more money from their NEC; and (2) The Annual Public Fund (APF) distribution inside each Brazilian party depends on (a) the size of the electoral district, (b) the percentage of Federal Deputies elected in each state by the party; and, (c) the presence of regional directors in the Party\'s NEC. Our results suggest that the treatment\'s effect (having a current or former regional director into its\' party\'s NEC) on the amount of Annual Public Fund received from its\' NEC, is particularly strong in Parties that do not compete for the National Office. These results provide more evidence that Brazilian political parties differentiate themselves not only regarding their electoral strategies, but also regarding their internal organisation.